2008
DOI: 10.1111/j.1461-0248.2008.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐system synthesis of consumer and nutrient resource control on producer biomass

Abstract: Nutrient availability and herbivory control the biomass of primary producer communities to varying degrees across ecosystems. Ecological theory, individual experiments in many different systems, and system-specific quantitative reviews have suggested that (i) bottom-up control is pervasive but top-down control is more influential in aquatic habitats relative to terrestrial systems and (ii) bottom-up and top-down forces are interdependent, with statistical interactions that synergize or dampen relative influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
429
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(466 citation statements)
references
References 166 publications
(378 reference statements)
34
429
3
Order By: Relevance
“…Bars with the same letter within each panel do not significantly differ at the P < 0.01 level based on Tukey contrasts (corrected for multiple comparisons). food web structure (15,17,24), the effects of which may be as great as those of plant diversity. For example, although algal biomass production increased with algal diversity in a study of a benthic marine community, this effect was masked when herbivores were present because, in this case, the increased production was consumed by herbivores (15).…”
Section: Discussionmentioning
confidence: 99%
“…Bars with the same letter within each panel do not significantly differ at the P < 0.01 level based on Tukey contrasts (corrected for multiple comparisons). food web structure (15,17,24), the effects of which may be as great as those of plant diversity. For example, although algal biomass production increased with algal diversity in a study of a benthic marine community, this effect was masked when herbivores were present because, in this case, the increased production was consumed by herbivores (15).…”
Section: Discussionmentioning
confidence: 99%
“…survival, growth, abundance, behaviour e.g. species diversity, biomass, total primary production additive antagonistic Crain et al [15] Darling & Côté [16] Dieleman et al [32] Gruner et al [26] Harvey et al [47] Przelawski et al [22] Wu et al [31] Stephens et al [29] Wahl et al [33] Jackson [27] Figure 4. Links between various categories of responses to multiple stressors and the types of interactions occurring between these stressors.…”
Section: Can We Predict Stressor Interaction Types?mentioning
confidence: 99%
“…At the scale of our experiment, all main predators moved freely between the treatments and showed aggregation in habitat patches with vegetation, clearly demonstrating that predators did not distribute passively. Interestingly, a survey of manipulative experiments revealed that the marine benthos is the only ecosystem in which grazers generally show an increase with nutrient enrichment and where cascading effects on lower trophic levels from predator removal are the strongest (Borer et al 2005(Borer et al , 2006Gruner et al 2008). Thus, the marine benthos seems to be vulnerable to cascading behavior between trophic levels, which may be promoted by the common conditions of highly mobile predators and a dominance of continuously reproducing and well-mixed distributions of producers (Nisbet et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of trophic cascades depends on strong consumer control of the prey community, with a cascading indirect positive effect being generated on the next lower trophic level. There are a number of distinct species traits that determine if species are subjected to consumer control (Duffy and Hay 1990;Coley and Barone 1996;Polis 1999;Hopcraft et al 2010), and the response of the community to changes in predators should ultimately depend on the community composition of each trophic level (Gruner et al 2008). Our results support the concept that the lifestage development of the producer trophic level can be essential for responses to predator declines in the marine benthos, by demonstrating that established larger macroalgae were resource controlled regardless of the composition of the higher trophic levels.…”
Section: Factormentioning
confidence: 99%